"É possível, mas agora n\~ao": A demoratizaç\~ao da justiça no cotidiano dos advogados populares - Fabio de Sá e Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– People's lawyers constitute an organized segment of the Brazilian bar that provides legal assistance to social movements and, as it is said in the very way this population designates itself, advocates for the causes of the people. This article discusses whether the Brazilian justice system is permeable to the interests and expectations of the various social groups, especially the poor and disadvantaged. To do so, the article examines narratives about the everyday experiences of so-called people's lawyers within the justice system, with a special focus on lawyers who advocate for groups involved in struggles for land - the landless, the z, and the indigenous peoples. As its main findings, the article presents three crucial tensions that people's lawyers face and that were more salient in the data analysis. One gravitates around the definition of the applicable law, and refers to what lawyers consider to be an unawareness of or a disregard for legal rules that are favorable to their client groups by justice officials. Another tension gravitates around biases in the justice system, and refers to the perception, among people's lawyers, that justice officials have strong links or common interests with the issues or actors that they are supposed to be ruling against, such as big landowners. The last one refers to the relationships of power and hierarchy that subsist in the Brazilian legal profession and amount to actual prejudice against people's lawyers within the bar. In light of these findings, the article argues that the democratization of the justice system is an integral part of the structure of opportunities for the development of public interest law advocacy, and suggests an academic and political agenda around that issue in Brazil.
Keywords: Z; Z0; 330